Identification of differentially methylated BRCA1 and CRISP2 DNA regions as blood surrogate markers for cardiovascular disease - Geoffrey Istas (Nature Portfolio, 2017)
Abstract Genome-wide Illumina InfiniumMethylation 450 K DNA methylation analysis was performed on blood samples from clinical atherosclerosis patients (n = 8) and healthy donors (n = 8) in the LVAD study (NCT02174133, NCT01799005). Multiple differentially methylated regions (DMR) could be identified in atherosclerosis patients, related to epigenetic control of cell adhesion, chemotaxis, cytoskeletal reorganisations, cell proliferation, cell death, estrogen receptor pathways and phagocytic immune responses. Furthermore, a subset of 34 DMRs related to impaired oxidative stress, DNA repair, and inflammatory pathways could be replicated in an independent cohort study of donor-matched healthy and atherosclerotic human aorta tissue (n = 15) and human carotid plaque samples (n = 19). Upon integrated network analysis, BRCA1 and CRISP2 DMRs were identified as most central disease-associated DNA methylation biomarkers. Differentially methylated BRCA1 and CRISP2 regions were verified by MassARRAY Epityper and pyrosequencing assays and could be further replicated in blood, aorta tissue and carotid plaque material of atherosclerosis patients. Moreover, methylation changes at BRCA1 and CRISP2 specific CpG sites were consistently associated with subclinical atherosclerosis measures (coronary calcium score and carotid intima media thickness) in an independent sample cohort of middle-aged men with subclinical cardiovascular disease in the Aragon Workers’ Health Study (n = 24). Altogether, BRCA1 and CRISP2 DMRs hold promise as novel blood surrogate markers for early risk stratification and CVD prevention.